Case Report: Metastatic small bowel adenocarcinoma with DNA mismatch repair deficiency in an organ transplant recipient treated with anti-PD-1 immunotherapy - Phung, Quan H.; Tsai, Alexander K.; Park, Byoung U.; Schat, Robben; Spong, Richard; Tsai, L. Jill; Kulkarni, Amit A.; Antonarakis, Emmanuel S.; Gupta, Arjun (Frontiers in Oncology, 2025)
We present a case of a 65-year-old woman with a history of kidney and pancreas transplants for type 1 diabetes mellitus who presented with small bowel obstruction and was found to have a poorly differentiated small bowel adenocarcinoma with multifocal osseous and nodal metastases. Plasma-based next generation circulating tumor deoxyribonucleic acid (DNA) sequencing revealed mismatch repair deficiency and an exceptionally high tumor mutational burden (TMB) of 1069 mutations/megabase (mut/Mb). Initial management consisted of cytotoxic chemotherapy (FOLFOX; 5-fluorouracil, leucovorin, and oxaliplatin) given the urgent need for a clinical response. Following multidisciplinary discussion and shared decision-making, nivolumab was added with cycle 3 of FOLFOX. Transplant-related immunosuppression was adjusted, and pancreas and kidney transplant function were monitored closely. Potential organ rejection was monitored using donor-derived cell-free DNA. Immune-related adverse events were not observed. After 5 cycles of treatment (3 cycles involving nivolumab), she achieved a complete clinical, molecular, and radiographic response. There was minimal evidence of allograft rejection without signs of dysfunction. Treatment was discontinued and subsequent surveillance imaging suggested durable remission for at least 9 months following treatment cessation. This case highlights the importance of genomic testing and targeting actionable molecular alterations in patients with rare cancers, as well as the role of multidisciplinary care.